Preparation of ¹⁸F-NaF radiopharmaceuticals using home-made automatic synthesis module at Hanoi Irradiation Center - Tran , Manh Thang; Mai , Van Vinh; Dam, Thi Tam; Nguyen , Quang Anh; Le , Thi Thu Hien; Pham , Minh Duc; Nguyen , Tuan Anh; Nguyen , Van Sy; Nguyen , Thanh Hung; Dang, Quang Bao; Nguyen , Xuan Vinh; Nguyen , Thi Kim Dung (Nuclear Science and Technology, 2019)
The aim of this study is to prepare 18F-NaF radiopharmaceutical using a home-made automatic synthesis module consisting of hardware and software which was made by a researcherteam of Hanoi Irradiation Center, HIC, Hanoi, Vietnam. Fluorine-18 isotopes produced in cyclotron KOTRON13 were transferred to the module and radioactive cation impurities were first removed by cation exchange on a carboxymethyl cation exchange (CM) cartridge, and then 18F- ion were trapped by a quaternary methyl ammonium anion exchange (QMA) cartridge. Finally, 18F- was eluated from the cartridge by isotonic saline water (NaCl 0,9% in water) in the form of 18F-NaF. Time of the preparation process was about 13 minutes. Radiochemical yield of the preparation was as high as 95.5%, in average. The qualities of the product were satisfied the criteria of the United States Pharmacopoeia (USP38). PET/CT bone scaner (skeletal scintigraphy) pre-clinical tests using of the 18 F-NaF product showed good quality of imaging for the entire skeletal and distribution of the 18F-NaF in the kidney and the bladder agreed with it’s natural distribution.